Selection for representative environment to identify high yielding and sweetness levels of sweet potato (Ipomoea batatas L.) in Indonesia - ESO SOLIHIN; DWI ANDREAS SANTOSA; BUDI NUGROHO; PURWONO PURWONO; RIJA SUDIRJA; HARIS MAULANA; NADIA NURANIYA KAMALUDDIN; AGUNG KARUNIAWAN; SYAIFUL ANWAR (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Solihin E, Santosa DA, Nugroho B, Purwono, Sudirja R, Maulana H, Kamaluddin NN, Karuniawan A, Anwar S. 2024. Selection for representative environment to identify high yield and sweetness levels of sweet potato (Ipomoea batatas) in Indonesia. Biodiversitas 25: 386-391. Sweet potato is one of the important and commercial agricultural commodities in the world. Yield and sweetness levels are important traits that can influence consumer preferences. Environment is an important factor in the development of sweet potatoes. A suitable environment will provide high yields and good quality. The objectives of this study were to examine the significance and relevance of sweet potato yield and sweetness levels in two locations (Sumedang and Bandung District) and to select representative environments for sweet potato yield and sweetness levels. The research was conducted in Sumedang and Bandung districts on lowland paddy field and dry land. The field experiment used a factorial randomized completed block design with three repetitions. The significance and relevance of sweet potato yield and sweetness levels was analysis using T-test. Representative environments were identified by GGE biplot. The results showed that the Bandung and Sumedang environments showed significant differences in yield but not in sweetness. The Bandung paddy field is the most representative environment for yield, while the Sumedang dry field and Bandung dry field are the most representative environments for sweetness. The results of this research can be used by researchers, farmers and industrial users in the sweet potato development program, especially the yield and yield quality.